2015
DOI: 10.1089/hgtb.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

Site-Directed Mutagenesis of Surface-Exposed Lysine Residues Leads to Improved Transduction by AAV2, But Not AAV8, Vectors in Murine Hepatocytes In Vivo

Abstract: The ubiquitin-proteasome pathway plays a critical role in the intracellular trafficking of recombinant adeno-associated virus 2 (AAV2) vectors, which negatively impacts the transduction efficiency of these vectors. Because ubiquitination occurs on lysine (K) residues, we performed site-directed mutagenesis where we replaced each of 10 surface-exposed K residues (K258, K490, K507, K527, K532, K544, K549, K556, K665, and K706) with glutamic acid (E) because of similarity of size and lack of recognition by modify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…administration. These data are consistent with our recently published studies, 62 suggesting that the ubiquitination/proteasome machinery involved in processing the Y-F mutant AAV8 vectors might be different between pancreas and liver, and that the use of lower dose of Y447F+Y733F-AAV8 might also minimize undesired host immune responses to the WT-AAV8 vectors, as has been occasionally observed in human clinical trial. 20,58 Prior whole body distribution studies have observed a discrepancy between the AAV vg copy number and overall gene expression delivered by AAV vectors.…”
Section: Discussionsupporting
confidence: 92%
“…administration. These data are consistent with our recently published studies, 62 suggesting that the ubiquitination/proteasome machinery involved in processing the Y-F mutant AAV8 vectors might be different between pancreas and liver, and that the use of lower dose of Y447F+Y733F-AAV8 might also minimize undesired host immune responses to the WT-AAV8 vectors, as has been occasionally observed in human clinical trial. 20,58 Prior whole body distribution studies have observed a discrepancy between the AAV vg copy number and overall gene expression delivered by AAV vectors.…”
Section: Discussionsupporting
confidence: 92%
“…Modification of capsid surface lysine residues also increased transduction efficiency of AAV2 vectors. 75 Tyrosine-modified AAV vectors have been used in clinical trials 76 and efficiently deliver genes to the retina and TM in rodents. Thus, proteasome inhibition or avoidance is one potential way to increase transduction efficiency with viral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…The elegant simplicity of rAAV vectors has led many researchers to focus on creating new derivatives of this system for gene transfer (100). A naked icosahedral capsid of ~25 nm in diameter can hold ~5 kb of single‐stranded DNA, which seems to be the minimal unit of transfer of genetic material that is likely to result in the transfer of a full‐expression cassette.…”
Section: Future Directionsmentioning
confidence: 99%